2022
DOI: 10.1002/ece3.9558
|View full text |Cite
|
Sign up to set email alerts
|

Wetland characteristics affect abundance and diversity of wintering birds: A case study in South‐Western Iran

Abstract: Water availability is an important driver of bird population change, and its effects are likely to increase in coming decades under climate change. Here we assess effects of temperature, precipitation, and water area on wintering bird populations in Miyangaran Wetland in southwestern Iran. Modeling methods including, generalized linear model (GLM) and hierarchical partitioning were used to examine the relative importance of variables. The number of wintering species, inhabiting the wetland, varied among years,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…Consequently, sh and other food resources for birds are seriously affected during the pick dry seasons which in turn affected the diversity of species. Similarly (Desta et al, 2021;Gaona et al, 2021;Malekian et al, 2022;Awash and Tekalign, 2023b) reported that Seasonal variations in the quantity of food resources and the unique seasonality of rainfall led to seasonal shifts in the quantity of birds.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, sh and other food resources for birds are seriously affected during the pick dry seasons which in turn affected the diversity of species. Similarly (Desta et al, 2021;Gaona et al, 2021;Malekian et al, 2022;Awash and Tekalign, 2023b) reported that Seasonal variations in the quantity of food resources and the unique seasonality of rainfall led to seasonal shifts in the quantity of birds.…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, there is another bird species assessment carried out in riverine and wetland habitats (Aynalem and Bekele, 2008), (Tefera et al, 2022). Previous studies emphasized the importance of wetlands for waterbirds and pointed out that a sustainable conservation plan is of paramount to protect the degradation of wetlands (Hailu and Megersa, 2021;Dixon et al, 2021;Malekian et al, 2022;Sheta et al, 2023;Awash and Tekalign, 2023). This study includes new sites which were not addressed earlier.…”
Section: Introductionmentioning
confidence: 99%
“…Both of these birds are water birds, using dams and other water sources for feeding and/or nesting (Hockey et al 2005) and it is therefore not surprising that they were only seen at the marshes. Water availability is known to be an important factor in determining bird population characteristics, with water area playing a particularly important role in affecting the structure of bird diversity and abundance (Malekian et al 2022). However, when creating artificial wetlands, instead of one large wetland, many smaller wetlands interspersed with more terrestrial habitats, such as the grassland sections in this study, can increase overall bird species richness by increasing landscape heterogeneity (Kačergytė et al 2021).…”
Section: A B Cmentioning
confidence: 91%